2008
DOI: 10.1007/s12160-008-9061-8
|View full text |Cite
|
Sign up to set email alerts
|

Course of Distress in Breast Cancer Patients, Their Partners, and Matched Control Couples

Abstract: Background Previous studies offer a limited perspective on the dynamic course of distress in cancer patients and their partners, owing to a restricted number of assessment points and the absence of comparison controls drawn from the general population. Purpose This study investigated the course of distress among breast cancer patients and their partners (N=92 couples) in comparison to matched control couples (N=64). Furthermore, the influence of neuroticism on distress was investigated. Method The Hospital Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 50 publications
4
69
1
1
Order By: Relevance
“…Cancer patients' partners' anxiety and depression levels have been associated with partners' neuroticism (Hinnen et al, 2007;Hinnen et al, 2008;Kim, Duberstein, Sörensen, & Larson, 2005;Nijboer, Tempelaar, Triemstra, van den Bos, & Sanderman, 2001). Partners' personality may not only determine partners' levels of psychological distress, but could possibly explain partners' needs for information and support, as neuroticism has been associated with cancer patients' caregivers' need for knowledge about the disease (Ferrario et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer patients' partners' anxiety and depression levels have been associated with partners' neuroticism (Hinnen et al, 2007;Hinnen et al, 2008;Kim, Duberstein, Sörensen, & Larson, 2005;Nijboer, Tempelaar, Triemstra, van den Bos, & Sanderman, 2001). Partners' personality may not only determine partners' levels of psychological distress, but could possibly explain partners' needs for information and support, as neuroticism has been associated with cancer patients' caregivers' need for knowledge about the disease (Ferrario et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although some partners appear to manage the confrontation with cancer rather successfully (Hinnen et al, 2008) or even find benefit from the caregiving experience (Kim, Schulz, & Carver, 2007), several studies indicate that intimate partners experience difficulties in dealing with cancer. Considerable proportions of spouses of cancer patients report significant psychological distress (Bergelt, Koch, & Petersen, 2008;Goldzweig et al, 2010;Hagedoorn, Sanderman, Coyne, Bolks, & Tuinstra, 2008;Pitceathly & Maguire, 2003;Wagner, Bigatti, & Storniolo, 2006), symptoms of depression (Bigatti, Wagner, Lydon-Lam, Steiner, & Miller, 2011;Segrin & Badger, 2010), and anxiety (Hodgkinson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study on lung cancer patients' concerns, women tended to report a significantly larger number of concerns than men [71]. Few studies that have examined distress in couples coping with cancer included a comparison group [72,73]. These studies revealed higher levels of distress among women in couples coping with cancer, regardless of whether they were the individuals with cancer or the partners.…”
Section: Caregiver's and Patient's Attachment Pattern Interactionsmentioning
confidence: 99%
“…Most couples do not report a decrease in the quality of their marital relationship (Manne, 1998), and only a small proportion of couples experience difficulties or separation following diagnosis (Dorval, Maunsell, Taylor-Brown, & Kilpatrick, 1999;Taylor-Brown et al, 2000). In addition, many couples report a strengthening of their relationship (Dorval et al, 2005;Hinnen et al, 2008) and the occurrence of positive changes or relational growth after this experience (Weiss, 2004). Therefore, the perception of increased marital intimacy among the spouses of cancer patients may reflect this general process of relationship enhancement that is observed among many couples.…”
Section: The Partner Experience Of Breast Cancermentioning
confidence: 99%